Environmental preferences of adolescents within a low ecological footprint country - Bogner, Franz X.; Suarez, Bosque Rafael (Frontiers in Psychology, 2022)
As Cuba achieves one of the lowest per capita ecological foot prints in the world (Global Footprint 2020), the country’s overshoot day in 2019 was on December 1st while some European countries already reach this limit in February (e.g. Luxembourg), monitoring the environmental preferences of the Cuban younger generation may offer valuable behavioural or pedagogical insights into such a society. As accepted standardized measures exist in the scales of 2-MEV (2- Major Environmental Values) and the GEB (General Ecological Behaviour), both measures are following the necessary psychometric requirement, as they have the unique advantage of repeated independent confirmation (and thus provide an external validity). These capture with 40 items of reported behaviour originating in six subscales that total in a single main cover score. The first one (2-MEV) monitors individual biocentric and anthropocentric preferences with a 20 item-set by relying upon these two higher order factors of ‘Preservation’ and ‘Utilisation’. Although many language versions already exist (33 in the case of the 2-MEV) for assessing the expected structure of these two as well as verifying validities and reliabilities of both scales, a country such as Cuba may affirm that this is due to expected cultural differences as well as their exceptionally low global footprint. Additionally “connectedness with nature”, and the “Morningness-Eveningness Scale for Children” (MESC) was included in this study (the latter one monitors the diurnal preferences of individuals). The responses of 348 Cuban secondary school students were subsequently subjected to various analyses including a linear structural model procedure. While expected psychometric structures of both scales were confirmed, neither the connectedness with nature nor the MESC show a substantial relationship to them. Nevertheless, all the regression scores follow the expected positive or negative directions, albeit not all the fit scores turned out as satisfactorily. Apparently, the applied measures secure a good basis for measuring the attitudinal and behavioural framework, but will need further fine tuning to completely monitor the environmental preferences of Cuban adolescents.